2013
DOI: 10.1210/jc.2013-2467
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT Characterization of Oral Activity on Radioiodine Scintigraphy

Abstract: Focal oral activity on diagnostic radioiodine scans frequently localizes to high-attenuation dental material on SPECT/CT. We postulate that an affinity between negatively charged iodide ions (I(-)) in saliva and positively charged metal ions (eg, Ag(+), Hg(+), Au(2+), Pd(2+)) within the dental materials is at the basis of persistent focal radioiodine uptake in the oral cavity. This represents a new mechanism underlying benign radioiodine activity not previously described in the medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Another commonly seen finding on radioiodine scintigrams is radiotracer activity in the region of the oral cavity, corresponding to tracer retention in dental amalgam (Fig 12). A proposed mechanism is retention of radioiodine because of the interaction of negatively charged iodide ions with positively charged metal ions within dental restoration materials (48). Other causes of radioiodine retention are listed in the Table.…”
Section: Radioiodine Retentionmentioning
confidence: 99%
“…Another commonly seen finding on radioiodine scintigrams is radiotracer activity in the region of the oral cavity, corresponding to tracer retention in dental amalgam (Fig 12). A proposed mechanism is retention of radioiodine because of the interaction of negatively charged iodide ions with positively charged metal ions within dental restoration materials (48). Other causes of radioiodine retention are listed in the Table.…”
Section: Radioiodine Retentionmentioning
confidence: 99%
“…One of the most commonly seen materials with this behavior is dental amalgam (Fig. 5a) [80,81]. The proposed mechanism of tracer retention demonstrated by in-vitro binding assays is the interaction and chemical binding of negatively charged iodide ions to the positively charged metal ions [80,81].…”
Section: Direct Rai Bonding To Metallic Foreign Bodiesmentioning
confidence: 99%
“…Two papers independently reported the utility of SPET-CT for investigation of a physiological mechanism of radioiodine uptake not previously described in the literature. Savas and colleagues reviewed 216 SPET-CT scans and found that oral radioiodine uptake was present on 123 (57 %) [79] and postulated an affinity of radioiodine for metals via a semi-permanent chemical reaction. Others studied 58 post-therapy patients with SPET-CT and confirmed that 91 % showed focal radioiodine localizing to dental restorations [80].…”
Section: Spet-ct Diagnostic Interpretationmentioning
confidence: 99%